(untitled) (Journal of Educational Sciences, 2018)
The process of integration into the global educational system requires a primary formation of professional readiness to carry out professional activities through the language of cooperation with other societies. Without the competent knowledge of foreign vocational-sectorial language such cooperation is not possible. This article examines a foreign vocational-sectorial communicative competence as the main component of a foreign language training of students. The particular emphasis is placed on the description of a foreign vocational-sectorial communicative competence in the field of professional activity in relation to the training of students of non-language higher school. The article deals with the model of shaping foreign vocational-sectorial communicative competence that can be used in language teaching process. It is noted that the model is being worked out and may be integrated into curricula. The main method of the research is the analysis of theoretical sources and empirical data. Our experiment has been conducted within the framework of the discipline «Vocationally-oriented foreign language» (2 credits), where second-year students of the specialty «State and local government» have been trained in two groups: a control group (20 students) and an experimental group (46 students). To check and to confirm the results, we attracted the same 46 students who continued their education within the framework of the discipline «Specialized foreign language», that contains 4 credits on the 3rd year of study and 2 credits on the 4th year of study, allocated from a higher education component. Key words: foreign vocational-sectorial education, a communicative competence, foreign language communication problems, foreign language vocational-sectorial communication.